9x+9=6-(8x-4)

Simple and best practice solution for 9x+9=6-(8x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x+9=6-(8x-4) equation:


Simplifying
9x + 9 = 6 + -1(8x + -4)

Reorder the terms:
9 + 9x = 6 + -1(8x + -4)

Reorder the terms:
9 + 9x = 6 + -1(-4 + 8x)
9 + 9x = 6 + (-4 * -1 + 8x * -1)
9 + 9x = 6 + (4 + -8x)

Combine like terms: 6 + 4 = 10
9 + 9x = 10 + -8x

Solving
9 + 9x = 10 + -8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8x' to each side of the equation.
9 + 9x + 8x = 10 + -8x + 8x

Combine like terms: 9x + 8x = 17x
9 + 17x = 10 + -8x + 8x

Combine like terms: -8x + 8x = 0
9 + 17x = 10 + 0
9 + 17x = 10

Add '-9' to each side of the equation.
9 + -9 + 17x = 10 + -9

Combine like terms: 9 + -9 = 0
0 + 17x = 10 + -9
17x = 10 + -9

Combine like terms: 10 + -9 = 1
17x = 1

Divide each side by '17'.
x = 0.05882352941

Simplifying
x = 0.05882352941

See similar equations:

| 39x=64x+24 | | 10x+12+4x-3= | | 5y-6+y+53=8y+50-5y | | 13t-2=3t+38 | | 11f=5f+36 | | 6(4x-8)=32 | | -8=2c-3c | | xy=120 | | 6-3(6-6x)=0 | | 3.2x+6.5=9.2+11x | | v^2-6v=20+2v | | (3+6)+4=3+(6+4) | | 1(x-4)=-5 | | 2(x+5.75)=15.275 | | 69.8x+42=65 | | 12/k=24k | | 120x+10=150x+4 | | 4x(2)-6x= | | 69.8+42=65 | | 2(x+3)+1=15 | | 56.80x+25.50=78x+100 | | 8x-15y=34 | | A=150*sqrt(3) | | 2(x+1)-5x=2x-8 | | F(x)=x/5-2x | | (2x-3y)(3x+6y)=0 | | 2x-5/6=6 | | (x-y)(x+2y)=0 | | x=2x^2+8x-16 | | (5-1)-2=5-(1-2) | | s-0.2=48 | | 6x+9=9-(3x-5) |

Equations solver categories